2021
DOI: 10.1002/jper.19-0441
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation of the periodontium associates with risk of future cardiovascular events

Abstract: Background: While growing evidence suggests a link between periodontal disease (PD) and cardiovascular disease (CVD), the independence of this association and the pathway remain unclear. Herein, we tested the hypotheses that: (1) inflammation of the periodontium (PD inflammation) predicts future CVD independently of disease risk factors shared between CVD and PD, and (2) the mechanism linking the two diseases involves heightened arterial inflammation. Methods: 18 F-fluorodeoxyglucose positron emission tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 57 publications
0
46
0
2
Order By: Relevance
“…Two main characteristics of periodontitis, chronic low-grade inflammation state and potential hematogenous dissemination of bacteria and their endotoxin, such as lipopolysaccharide, may explain the association between periodontal diseases and systemic conditions [ 2 – 4 ]. Particularly, severe periodontitis cases are at higher risk for cardiovascular disease, acute myocardial infarction, and stroke [ 5 ]. Furthermore, the bidirectional relationship between diabetes mellitus and periodontitis is well established, and it is now included in the classification of periodontitis to predict the risk of progression [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two main characteristics of periodontitis, chronic low-grade inflammation state and potential hematogenous dissemination of bacteria and their endotoxin, such as lipopolysaccharide, may explain the association between periodontal diseases and systemic conditions [ 2 – 4 ]. Particularly, severe periodontitis cases are at higher risk for cardiovascular disease, acute myocardial infarction, and stroke [ 5 ]. Furthermore, the bidirectional relationship between diabetes mellitus and periodontitis is well established, and it is now included in the classification of periodontitis to predict the risk of progression [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides having common risk factors, a mechanism linking the two diseases has been elucidated in a recent longitudinal study. Van Dyke et al (38) evaluated the F-fluorodeoxyglucose positron emission tomography/computed tomography of 304 individuals, quantifying periodontal and arterial inflammation. The authors showed that periodontitis is associated with arterial inflammation and that periodontitis predicted subsequent major adverse cardiovascular events (38).…”
Section: Discussionmentioning
confidence: 99%
“…Van Dyke et al (38) evaluated the F-fluorodeoxyglucose positron emission tomography/computed tomography of 304 individuals, quantifying periodontal and arterial inflammation. The authors showed that periodontitis is associated with arterial inflammation and that periodontitis predicted subsequent major adverse cardiovascular events (38). These findings corroborate the main results of our study, which underscore the hypothesis that periodontitis could influence the occurrence and treatment of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific meta-analytic studies have found a strong and consistent evidence that PD is associated with atherosclerosis [18] and an increased risk of future CVD events [19]. PD may also worsen pre-existing CVD [20] and treatment of PD appears to diminish CVD risk or its progression [21].…”
Section: Discussionmentioning
confidence: 99%